Report on visit from Prof. Kim Lutzen: Friday, 6 November 1998, Korolinska Institute (dept of nursing) Stockholm, Sweden - Kim Lutzen (AOSIS, 1999)
Prof. Kim Lutzen contacted the Department of Advanced Nursing Sciences, Unisa, via the Department's Web Page. Prof. Lutzen is the Chair of the Department of Nursing, which offers undergraduate, master and doctoral programmes. This Department of Nursing is situated within the Karolinska Institute, which comprises 29 Departments of Health Sciences, including a number of Medical Departments, Dentistry, Occupational Therapy, Physiotherapy, and Nursing. Prof. Lutzen emphasised that there is no Swedish phrase similar to "nursing science", consequently this t e n seems to be somewhat unfamiliar to the Swedish nurses. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.